Building Resilience in Qualitative Research: Challenges and Opportunities in Times of Crisis - Maine Suadik (International Journal of Qualitative Methods, 2022)
The COVID-19 pandemic has significantly impacted qualitative researchers, especially those whose research involves face-to-face interactions with the community in the field. Implementing various mitigation measures to prevent the spread of COVID-19 entailed modifying, postponing and/or cancelling many research projects. Based on the attributes of the COVID-19 pandemic, which are unpredictable and pose serious threats, developing a highly structured and tested data collection approach that can reflect experiences and social realities from ‘below’ during a crisis is necessary. As the latest global crisis marker of this millennium, the extent of the impact of the COVID-19 pandemic on the knowledge production process in marginalised indigenous communities is largely unknown. This study contributes to the debate on how to ensure qualitative research methods possess the flexibility and adaptability to study such communities during a crisis.